Ceftazidime-Avibactam in Combination with Imipenem as Salvage Therapy for ST11 KPC-33-Producing Klebsiella pneumoniae - Li Ding; Siquan Shen; Renru Han; Dandan Yin; Yan Guo; Fupin Hu (MDPI AG, 2022)
A 22-year-old man, after a hematopoietic stem cell transplant, suffered long-term pneumonia caused by blaKPC-2-positive K. pneumoniae and blaKPC-33-positive K. pneumoniae alternately and finally achieved pathogenic clearance and improvement of clinical infectious conditions after using ceftazidime-avibactam in combination with imipenem as salvage therapy. This case provides a reference for treating infection caused by K. pneumoniae with a KPC variant in countries lacking new antimicrobial agents.